THE EFFECT OF ENVIRONMENTAL FACTOR AND USE OF PERSONAL PROTECTIVE EQUIPMENT ON THE SYMPTOMS OF ACUTE RESPIRATORY TRACT INFECTIONS IN FURNITURE INDUSTRY WORKERS - Merry Sunaryo (JURNAL INDONESIA DARI ILMU LABORATORIUM MEDIS DAN TEKNOLOGI, 2020)
Dust is one type of potential hazardzs in the workplace that can affect the health of the workers. The occupation that are always exposed to dust is furniture industry workers so that they have higher risk of getting acute respiratory tract infection (ARI) disorder which can interfere with breathing. The wood dust is formed from some of the sawn wood and sanding that will lead to an acute respiratory tract infection. The study aimed to determine the effect of environmental factor and the use of Personal Protective Equipment (PPE) against the symptoms of acute respiratory infections in the furniture industry workers. The research method used was quantitative method with observational and cross-sectional research types and it was analysed by using logistic regression test. The population in this study was the workers of the furniture industry at Semarang street, Surabaya City, with a total of 57 people, of which 37 furniture workers as a sample. The results show that most of the workers has symptoms of acute respiratory tract infection. It could be influenced by the environmental factor such as dust exposure that produced wood dust in each manufacturing processes. Additionally, the use of PPE also affected the occurrence of acute respiratory tract infections symptoms in the workers. In conslusion, many factors can influence the occurrence of acute respiratory tract infection symptoms in the furniture industry workers. Therefore, it is necessary to minimize the dust exposure in workers by wearing PPE such as respirators.